STRATEGI CITY BRANDING DI MASA PANDEMI COVID-19: Studi Kasus See You in Seoul dengan Brand Ambassador BTS - Hanindharputri, Made Arini; Candra Valentino, Pande Putu Adi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
On this day, Covid-19 has become a pandemic that has hit all countries in the world. Each country has strict procedures to block access to the spread of the coronavirus, such as closing access to the country. However, in a situation like this the country continues to do branding with the hope that after the pandemic ends, both local and foreign people will continue to visit the country. South Korea, as a country that is routinely visited every year by tourists from all over the world, carries out a city branding campaign by cooperating with BTS (Bangtan Seoyeondan) as its brand ambassador. The strength of BTS with a very prominent brand image has made the See you in Seoul campaign get great attention from people around the world. The purpose of this article is to determine the city branding strategy during a pandemic by looking at the regional potential that can be presented virtually. The method used is descriptive qualitative by collecting visual content contained in the See You in Seoul campaign. The results of the analysis state that branding strategies with the increased brand image through brand ambassadors and regional potential are virtually effective in branding tourism during a pandemic so that tourists are still interested in visiting the area both virtually and directly after the pandemic ends.